Factors Associated with Patient’s Family Anxiety in the Intensive Care Unit (ICU) - Herlina Herlina; Ifa Hafifah; Noor Diani (University of Muhammadiyah Malang, 2020)
Introduction: Critical and life-threatening patients cause anxiety in the family, which may be caused by many factors such as age, education, experience, knowledge, attitudes, and so on. Objective: The purpose of this study was factors assosiated patient’s family anxiety in the ICU. Method: Correlation research with cross sectional approach. Samples amounted to 30 people with consecutive sampling technique. The instrument used questionnaires respondent characteristics, knowledge, health services, and HARS anxiety. Data analysis using the Spearman rank test. Result: There was a relationship of age (p = 0,000), level of education (p = 0,000), experience (p = 0,000), knowledge (p = 0,000), with the patient's family anxiety and no gender relationship (p = 0.163) and health services ( p = 0.334) with patient’s family anxiety in the ICU. Age, level of education, experience, and knowledge influence the patient's family anxiety. Discussion: It is recommended to hospitals to provide regular counseling between families and health professionals in the ICU, as well as provide leaflets about care in the ICU.